2019
DOI: 10.1037/tra0000427
|View full text |Cite
|
Sign up to set email alerts
|

Training community providers in evidence-based treatment for PTSD: Outcomes of a novel consultation program.

Abstract: Objective: Extensive research supports the use of prolonged exposure (PE) and cognitive processing therapy (CPT), for posttraumatic stress disorder (PTSD) in veterans and service members. PE and CPT have been disseminated nationally across the Department of Veterans Affairs (VA) facilities. Many service members and veterans receive care outside the VA where access to these gold standard psychotherapies can be limited. This paper presents a novel program developed to train community providers in the use of PE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Further, providing information about PE and dispelling concerns about PE may not be enough to shift beliefs to the extent necessary for increased uptake of exposure‐based treatments. This strategy may more effectively contribute to both belief change and increased utilization when implemented in the context of a broader training or in conjunction with other components critical in implementation, such as role plays, supervision on cases, and ongoing consultation (Charney et al, 2019). The gap between belief change and utilization in this study is an ongoing concern in exposure‐based therapies (Trivasse et al, 2020) and reflects the multifaceted nature of dissemination and implementation efforts that require addressing barriers and challenges at multiple levels (Michie et al, 2011; Weiner et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Further, providing information about PE and dispelling concerns about PE may not be enough to shift beliefs to the extent necessary for increased uptake of exposure‐based treatments. This strategy may more effectively contribute to both belief change and increased utilization when implemented in the context of a broader training or in conjunction with other components critical in implementation, such as role plays, supervision on cases, and ongoing consultation (Charney et al, 2019). The gap between belief change and utilization in this study is an ongoing concern in exposure‐based therapies (Trivasse et al, 2020) and reflects the multifaceted nature of dissemination and implementation efforts that require addressing barriers and challenges at multiple levels (Michie et al, 2011; Weiner et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This diversity can add additional complexity to the task of designing programs in support of EBT implementation. One effort to disseminate EBTs for PTSD to community providers in New England (Charney et al, 2019) found that providers who attended posttraining consultation were significantly more likely to implement EBTs for PTSD and complete treatment with patients 6 months after training. Learning collaboratives, which typically include team-based training, multiple in-person learning sessions, and posttraining consultation, have been shown to be effective in disseminating and sustaining behavioral health interventions (Nadeem et al, 2014).…”
Section: Training Programmentioning
confidence: 99%
“…Dissemination science recommends didactic training for clinicians in ESTs followed by a period of consultation with an expert (Karlin & Cross, 2014; Ruzek & Rosen, 2009). In one study, a 2-day training followed by consultation, compared to the 2-day training alone, resulted in greater implementation of PE and CPT in community practice and a greater number of case completions (Charney et al, 2019). Foa and colleagues found that consultation predicted increased provider-reported efficacy in using PE as well as patient speed of response and decreased PTSD symptoms at posttreatment (Foa et al, 2020).…”
mentioning
confidence: 99%
“…The VA consultation programming is facilitated by a top-down initiative that is not available in community practice. The effort by Charney et al (2019) to adopt a “moderate-touch” version of the VA consultation model for community practitioners is a valuable step that provides access to a lower-intensity form of consultation. However, the gold-standard, intensive consultation approach provided through the VA can only be attained in the community setting with a national network of well-trained and dedicated consultants.…”
mentioning
confidence: 99%